Prijedor: re-imagining the future - Mitrić, D; Musić, S (Refugee Studies Centre, University of Oxford, 2015)
Public memorialisation in Bosnia and Herzegovina today is an act of remembering not just those who died in the conflict but also the multi-ethnic reality of earlier times. Articulation of this, however, is being obstructed in cities like Prijedor.